2018
DOI: 10.1021/jacs.8b01876
|View full text |Cite
|
Sign up to set email alerts
|

Ground-State Copper(III) Stabilized by N-Confused/N-Linked Corroles: Synthesis, Characterization, and Redox Reactivity

Abstract: Stable square planar organocopper(III) complexes (CuNCC2, CuNCC4, and CuBN) supported by carbacorrole-based tetradentate macrocyclic ligands with NNNC coordination cores were synthesized, and their structures were elucidated by spectroscopic means including X-ray crystallographic analysis. On the basis of their distinct planar structures, X-ray absorption/photoelectron spectroscopic features, and temperature-independent diamagnetic nature, these organocopper complexes can be preferably considered as novel orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 91 publications
7
64
1
Order By: Relevance
“…[3,12] The core skeleton of Cu-5 adopted a quasi-planar geometry with a mean-plane deviation (m.p.d., defined by 23 core atoms) of 0.128 (Figure 2 d). More importantly, the N1-N19 bond length of Cu-5 was estimated to be 1.373 (4) , which was shorter than the corresponding C(sp 2 )-N(sp 2 ) bond length (1.377(3) ) in Cu-8 based on the intrinsic small radius of the nitrogen atom. [13] Furthermore, natural bond orbital (NBO) [14] analysis revealed that the Wiberg bond index of the N1-N19 bond moiety was 1.020, which was similar to that of the corresponding NÀC bond (1.072) in Cu-8.…”
Section: Corrolesareknownascontractedvariantsof18pporphyrinsmentioning
confidence: 79%
See 3 more Smart Citations
“…[3,12] The core skeleton of Cu-5 adopted a quasi-planar geometry with a mean-plane deviation (m.p.d., defined by 23 core atoms) of 0.128 (Figure 2 d). More importantly, the N1-N19 bond length of Cu-5 was estimated to be 1.373 (4) , which was shorter than the corresponding C(sp 2 )-N(sp 2 ) bond length (1.377(3) ) in Cu-8 based on the intrinsic small radius of the nitrogen atom. [13] Furthermore, natural bond orbital (NBO) [14] analysis revealed that the Wiberg bond index of the N1-N19 bond moiety was 1.020, which was similar to that of the corresponding NÀC bond (1.072) in Cu-8.…”
Section: Corrolesareknownascontractedvariantsof18pporphyrinsmentioning
confidence: 79%
“…Recently, we reported on a high-valent Cu III carbacorrole embedded with a peculiar a,b'-linked pyrrole unit. [4] Skeletal modification via the "N-confusion approach" resulted in the modulation of the Cu d x 2 Ày 2 orbital energy by the NNNC donor coordination environment. Copper benzonorrole (Cu-8, Figure 1 a) bearing an N(sp 2 )-C(sp 2 ) linkage, in turn, exhibited the characteristic features of a closed-shell singlet Cu III species, a highly planar geometry, diamagnetic property, and substantially up-shifted pre-edge energy in the X-ray absorption spectrum.…”
Section: Corrolesareknownascontractedvariantsof18pporphyrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Furuta and co‐workers reported a variety of N‐confused corrole copper complexes ( CuNCC2 , CuNCC4 , CuBN ) in which the NNNC‐coordinated copper (i.e. organocopper species) preferably took high valent copper(III) states …”
Section: Introductionmentioning
confidence: 99%